Pelayanan Sosial Berbasis Keluarga Bagi Anak Tunagrahita di Sekolah Dasar Luar Biasa Negeri 117709 Labuhanbatu - Ryan Aprilka L Tobing; Husni Thamrin (Yayasan Literasi Sains Indonesia, 2023)
Children with disabilities are children who need special treatment related to their condition. Mentally retarded children are part of children with disabilities who are characterized by a level of intelligence that is below the average child in general, this of course makes it difficult for mentally retarded children to develop and sosialize with the surrounding environment. In this case, sosial services are needed to help mentally retarded children grow and develop into independent children and at a minimum can sosialize with the surrounding environment. This research was conducted to see whether the sosial services carried out by the State Elementary School 117709 Labuhanbatu were implemented or not. Data collection techniques were carried out by literature study, observation, interviews and documentation. The data obtained in the field is then analyzed by the researcher and explained qualitatively, until finally conclusions can be drawn from this research. The results of this study indicate that sosial services for mentally retarded children at the State Elementary School 117709 Labuhanbatu have been implemented. The implementation of these sosial services is based on family values ​​which include mentoring, parenting skills and also providing nutrition.